2009
DOI: 10.1007/s10646-009-0453-8
|View full text |Cite
|
Sign up to set email alerts
|

Growth and antioxidant response in Hydrocharis dubis (Bl.) Backer exposed to linear alkylbenzene sulfonate

Abstract: A two-week exposure experiment was designed to investigate the toxicity of linear alkylbenzene sulfonate (LAS) on the aquatic plant Hydrocharis dubis (Bl.) Backer, focusing on growth, photosynthetic pigments and the activities of antioxidant enzymes. No significant differences were observed in the growth parameters of H. dubis when H. dubis was exposed to lower LAS doses (10 mg l(-1)) re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
31
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 40 publications
3
31
2
Order By: Relevance
“…2a), especially at high exposure concentrations (MCLR ≥3 g/ml, or LAS ≥20 g/ml or their mixture ≥3 + 10 g/ml), indicating that individual and joint exposure to the two toxicants in L. minor triggered antioxidant reactions. Increased SOD activity with MCLR treatment was consistent with other results [11,[48][49][50], but little research has focused on SOD activity after LAS exposure [24]. SOD activity was more strongly reduced after 8 d exposure compared with 2 d (Fig.…”
Section: Mclr ( G/ml)supporting
confidence: 90%
See 2 more Smart Citations
“…2a), especially at high exposure concentrations (MCLR ≥3 g/ml, or LAS ≥20 g/ml or their mixture ≥3 + 10 g/ml), indicating that individual and joint exposure to the two toxicants in L. minor triggered antioxidant reactions. Increased SOD activity with MCLR treatment was consistent with other results [11,[48][49][50], but little research has focused on SOD activity after LAS exposure [24]. SOD activity was more strongly reduced after 8 d exposure compared with 2 d (Fig.…”
Section: Mclr ( G/ml)supporting
confidence: 90%
“…In raw sewage, the range in LAS levels was 1-15 g/ml [44]. In China, the effluent standard of LAS in sewage plants is 10 g/ml [24]. In fact, many sewage effluents in China were out of the standard.…”
Section: Mclr ( G/ml)mentioning
confidence: 99%
See 1 more Smart Citation
“…Change in lipid peroxidation serves as a sensitive indicator of the extent of oxidative damage under stress in plant leaves, and also could be used as a toxicity bioassay for plants [35]. The results suggest that lower ClO 4 could have a negligible effect on these parameters for gannuoxiang.…”
Section: Antioxidant Defense Mechanisms Of Rice Varieties To Perchlormentioning
confidence: 97%
“…Superoxide dismutase and CAT activities decreased, but the contents of MDA increased in IR65598-112-2 at higher concentrations of ClO 4 -, but not in gannuoxiang. Increased CAT activity can be explained by an increase in substrate levels, such as evidence of an adaptive mechanism of the plants that serves to maintain the level of H 2 O 2 [35,37]. Increased POD activity indicated that exposure to ClO 4 induced the formation of H 2 O 2 , which in turn stimulated the biosynthesis of POD.…”
Section: Antioxidant Defense Mechanisms Of Rice Varieties To Perchlormentioning
confidence: 99%